2017
DOI: 10.1016/j.celrep.2017.09.078
|View full text |Cite
|
Sign up to set email alerts
|

UTX/KDM6A Loss Enhances the Malignant Phenotype of Multiple Myeloma and Sensitizes Cells to EZH2 inhibition

Abstract: Summary Loss or inactivation of the histone H3K27 demethylase UTX occurs in several malignancies, including multiple myeloma (MM). Using an isogenic cell system, we found that loss of UTX leads to deactivation of gene expression ultimately promoting the proliferation, clonogenicity, adhesion and tumorigenicity of MM cells. Moreover, UTX-mutant cells showed increased in vitro and in vivo sensitivity to inhibition of EZH2, a histone methyltransferase that generates H3K27me3. Such sensitivity was related to a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 41 publications
8
104
0
Order By: Relevance
“…Direct and indirect evidence suggests that KDM6A is sensitive to changes in oxygen levels within the cells . Inactivation of KDM6A is enriched in aggressive tumours, including PDAC . Interrogating the International Cancer Genome Consortium (ICGC) cohort, we found that a hypoxia transcriptional signature is enriched in PDAC characterised by KDM6A inactivation (see supplementary material, Figure S6A).…”
Section: Resultsmentioning
confidence: 78%
“…Direct and indirect evidence suggests that KDM6A is sensitive to changes in oxygen levels within the cells . Inactivation of KDM6A is enriched in aggressive tumours, including PDAC . Interrogating the International Cancer Genome Consortium (ICGC) cohort, we found that a hypoxia transcriptional signature is enriched in PDAC characterised by KDM6A inactivation (see supplementary material, Figure S6A).…”
Section: Resultsmentioning
confidence: 78%
“…In addition to the H3K37me2/3 demethylating function, KDM6A has been proposed to have demethylase‐independent functions in the regulation of gene expression through interacting with other transcriptional regulators (Van der Meulen et al , ; Ezponda et al , ). KDM6A can be a component of MLL2 complex, a histone H3K4 methyltransferase complex (Van der Meulen et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…6 Examples include UC, 49 lung cancer, 58 pancreatic squamous carcinoma, 32 multiple myeloma, 59 and some breast cancer cell lines. In several cancer types, inhibitors of the EZH2 methyltransferase like GSK126 are more efficacious in cell lines and mouse models with UTX loss of function.…”
Section: Clinical Applicationsmentioning
confidence: 99%